Maternal mortality review by three delay model: a retrospective study from a tertiary care hospital of Chhattisgarh - Jogi, Sangeeta R.; Ekka, Anju R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: SDG 3 includes an ambitious target of reducing the global MMR to less than 70 per 100 000 births by 2030. In order for effective initiation of measures to reduce maternal mortality it is necessary to assess the levels of delays, causes of death, health seeking behavior during antenatal and postnatal period and obstacles in reception of health services. Methods: Retrospective study of 112 maternal death cases from a tertiary medical centre (Medical College) was done. The details of all the maternal mortalities from January 2018 to July 2020 were collected from the individual case sheets, facility-based maternal death review form and MDR Case Summary. Results: The study reported a very high MMR of 802. Hypertensive disorders (36.61%), Obstetric haemorrhage (25.89%) and Sepsis (14.29%) constituted the major direct cause of maternal deaths whereas anaemia was the most common indirect cause (7.14%). First, second and third delays were present in 95.54%, 70.54% and 47.32% cases respectively. Conclusions: Suboptimal ANC, long distances to reach final hospitals, high number of referrals and admission during complicated stage explains the very high maternal mortality in the present study. Application of Three Delay Model revealed that most of the maternal death occurred due to delays in multiple levels and first delay was the most commonly identified delay. Accelerated efforts should be implemented to minimize all the delays in order to achieve SDG goals.